2012
DOI: 10.5455/ijavms.147
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of bluetongue virus antibodies in sheep in Kurdistan province in west of Iran

Abstract: The objective of this study was to describe the seroprevalence rates of bluetongue virus (BTV) in sheep in west and northwest provinces of Iran. Bluetongue virus, an economically important orbivirus of the Reoviridae family, causes a hemorrhagic disease mainly in sheep and occasionally in cattle and some species of deer. Bluetongue virus is transmitted between its mammalian hosts by certain species of biting midges (Culicoides spp.) and it can infect all ruminant species. Overall, 26 serotypes have been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…The present finding is found to be relatively lower than the previously reported seroprevalence to BTV in small ruminants by different authors in different countries such as 41.17% in small ruminants in Southern Ethiopia [ 13 ], 46.67% in sheep in central Ethiopia [ 9 ], 78.4% in small ruminants in Grenada [ 22 ] and 45.7% in small ruminant in India [ 23 ]. However, 30.6% seropositivity to BTV in small ruminants in the present study is comparatively higher than the reports of other researchers like 6.57% in sheep in Southeast Iran [ 21 ], 6.96% from small ruminants (13.7% in goats and 5.70% in sheep) in Algeria [ 24 ], 2.63 and 5.3% in small ruminants in Kerala and Karnataka (India) [ 25 , 26 ] respectively. In the present study, the difference in the seropositivity might be due to difference in animal species, age of sampled animals, immune status of sampled animals, agroclimatic zones, ecology, and types of culicoides vectors.…”
Section: Main Textcontrasting
confidence: 79%
See 1 more Smart Citation
“…The present finding is found to be relatively lower than the previously reported seroprevalence to BTV in small ruminants by different authors in different countries such as 41.17% in small ruminants in Southern Ethiopia [ 13 ], 46.67% in sheep in central Ethiopia [ 9 ], 78.4% in small ruminants in Grenada [ 22 ] and 45.7% in small ruminant in India [ 23 ]. However, 30.6% seropositivity to BTV in small ruminants in the present study is comparatively higher than the reports of other researchers like 6.57% in sheep in Southeast Iran [ 21 ], 6.96% from small ruminants (13.7% in goats and 5.70% in sheep) in Algeria [ 24 ], 2.63 and 5.3% in small ruminants in Kerala and Karnataka (India) [ 25 , 26 ] respectively. In the present study, the difference in the seropositivity might be due to difference in animal species, age of sampled animals, immune status of sampled animals, agroclimatic zones, ecology, and types of culicoides vectors.…”
Section: Main Textcontrasting
confidence: 79%
“…This findings is in agreement with the results of Gulima [ 10 ] who reported 34.1% seropositivity to BTV in indigenous sheep of Northwestern Ethiopia. The seropositivity to BTV in small ruminants (28.6%) in India [ 14 ], domestic livestock (23%) in Kazakhstan [ 15 ], sheep in Iran (35.9%) [ 16 ], sheep in Iran (34.93%) [ 17 ], goats in Iran (39.47%) [ 18 ], small ruminants in Turkey (29.5%) [ 19 ], sheep in Iran (37.7%) [ 20 ] and again sheep in Iran (33.75%) [ 21 ] has also been reported from other parts of the world.…”
Section: Main Textmentioning
confidence: 99%
“…Flocks of small ruminants are mainly managed under two different systems, namely, village and migratory (nomadic). Animals in both systems are mostly kept on natural grasslands and farmlands with little supplementary feeding and in a few cases, intensive systems of production are employed (Kamalzadeh et al, 2008), sheep and goat husbandry hygiene level (manure, pond, and stagnant water management), nutrition and animal welfare in village and migratory systems are less than in Intensive systems and the environmental conditions in village and migratory systems because of the presence of rivers, wet-lands such as the marshes, lakes, oasis and pools are suitable for the raise, survival and vectors activity. Therefore, graze based management can be a probable cause for the higher prevalence of disease in sheep and goats in Iran.…”
Section: Seroprevalence Of Bluetongue In Camelmentioning
confidence: 99%
“…Cattle, while commonly infected in endemic and epizootic areas, rarely develop clinical disease So, cattle are important in transmission and acting as reservoirs for the BTV (Constable et al, 2017). At present, there are around 8,000,000 of three categories of cattle breeds in Iran: pure exotic (the Holstein is the most popular and dominating breed) that kept in industrial and semi-industrial farms whose hygienic level are higher than traditional breeding systems and crossbred of native and exotics and pure native breeds that reared in most of villages under a traditional system (Kamalzadeh et al, 2008). Based on our results, the seroprevalence of bluetongue among cattle was 3.3% (95% CI= 0.06-15.0) in Iran.…”
Section: Seroprevalence Of Bluetongue In Camelmentioning
confidence: 99%
“…In Southern Europe, Turkey and Iran C. imicola is an important vector of BTV and in the warmer parts of these regions the short viraemia in farm animals does not limit the transmission of BTV because of the more favourable climatic conditions. No data for C. imicola in Kazakhstan could be found, although it has been found in northern Iran [27] just across the Caspian Sea. Modelling has suggested that favourable conditions for C. imicola may be present in the southern most parts of Kazakhstan [28].…”
Section: Discussionmentioning
confidence: 92%